DNA methylation biomarkers in cancer: progress towards clinical implementation. (June 2012) - Mikeska, Thomas; Bock, Christoph; Do, Hongdo; Dobrovic, Alexander
Altered DNA methylation is ubiquitous in human cancers and specific methylation changes are often correlated with clinical features. DNA methylation biomarkers, which use those specific methylation changes, provide a range of opportunities for early detection, diagnosis, prognosis, therapeutic stratification and post-therapeutic monitoring. Here we review current approaches to developing and applying DNA methylation biomarkers in cancer therapy. We discuss the obstacles that have so far limited the routine use of DNA methylation biomarkers in clinical settings and describe ways in which these obstacles can be overcome. Finally, we summarize the current state of clinical implementation for some of the most widely studied and well-validated DNA methylation biomarkers, including SEPT9, VIM, SHOX2, PITX2 and MGMT .